The Dynamics of Self-Esteem among Emerging Adults Experiencing Recurrent Parental Conflict: A Collective Case Study - Elsa Rahmadhea Prihastika; Rizka Lailatul Fitriyah; Fatimah Azzakiyah; Rahma Intan Nuraini (The Future of Education Journal, 2026)
This study aims to understand the dynamics of self-esteem among young adult female university students (aged 20–25 years) who have experienced recurrent parental conflict within intact families. Employing a qualitative approach with a collective case study design, data were collected through in-depth interviews with three participants selected using purposive sampling based on predetermined criteria and maximum variation, representing low, moderate, and high levels of self-esteem. The data were analyzed using thematic analysis. The findings revealed three distinct patterns. Participant 1 (low self-esteem) exhibited deeply rooted negative self-beliefs, perceived herself as unworthy and unloved, blamed herself for her parents' conflicts, and lacked a supportive social network. Participant 2 (moderate self-esteem) demonstrated fluctuating self-esteem that depended on situational factors and external validation, requiring support from significant others during periods of distress. Participant 3 (high self-esteem) displayed stable and resilient self-esteem, characterized by strong self-differentiation and an internal locus of control, viewed failures as opportunities for learning, and did not rely on external recognition for self-worth. The study concludes that the dynamics of self-esteem vary according to the quality of the parent–child relationship, social support, coping mechanisms, emotion regulation, self-differentiation, and locus of control. Individuals raised in similar family environments may develop different levels of self-esteem, highlighting the importance of interventions that strengthen internal validation and emotional resilience.